Identification of Mycobacterium avium complex in sarcoidosis. - el-Zaatari, F A (1996)
Cell wall-defective bacteria which later reverted to acid-fast bacilli have been isolated from sarcoid tissue. These have not been conclusively shown to be mycobacteria. Specific PCR assays were applied to identify mycobacterial nucleic acids in these cultured isolates and in fresh specimens obtained from patients with sarcoidosis. Positive amplification and hybridization were observed with Mycobacterium avium complex- and/or Mycobacterium paratuberculosis-specific probes in five of the six cultured isolates and two fresh skin biopsy samples and one cerebrospinal fluid specimen. There was no amplification or hybridization with Mycobacterium tuberculosis or M. avium subsp. silvaticum probes, respectively. Patients' sera were also tested for antibody reactivities by immunoblotting with M. paratuberculosis recombinant clones expressing the 36,000-molecular-weight antigen (36K antigen) (p36) and the 65K heat shock protein (PTB65K). All seven sarcoidosis, four of six tuberculosis, and all six leprosy patient serum specimens showed strong reactivity with p36 antigen. In contrast, 13 of 38 controls showed only weak reactivity with p36 (P = 0.002 for controls versus sarcoidosis samples). Similarly, PTB65K reacted with high intensity with sera from 5 of 5 sarcoidosis, 5 of 6 tuberculosis, and 5 of 6 leprosy patients, compared with its low-intensity reaction with 5 of 22 controls (P = 0.001 for controls versus sarcoidosis samples). This study demonstrates the isolation and/or identification of M. paratuberculosis or a closely related M. avium complex strain from sarcoid skin lesions and cerebrospinal fluid. Furthermore, the reactivity of antibodies in sarcoid patient sera against p36 and PTB65K antigens was comparable to the reactivity of sera obtained from patients with known mycobacterial disease. Collectively, these data provide further support for the theory of the mycobacterial etiology of sarcoidosis.